Resultado estrutural e impulso fiscal: Aprimoramentos metodológicos - Sérgio Wulff Gobetti; Rodrigo Octávio Orair; Frederico Nascimento Dutra (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper provides a survey of the methodologies for estimating the structural budget balance and the fiscal impulse, which highlights the recent international literature spread by European Commission studies (Havik et al., 2014; Carnot e Castro, 2015). From this theoretical background, the paper presents new estimates for the output gap and tax elasticities, as well as an analysis of the determinants that lie behind Brazilian fiscal deterioration - estimated at 3.3 percentage points of the GDP during 2008-2016 according to the below the line method (or 4.2 percentage points above the line). The paper also offers an original contribution by measuring how potential GDP's measurement errors (or their growth rates changes) influence the stability of the benchmark used by the conventional methodology in order to estimate the fiscal impulse. This, in turn, puts a question mark over the robustness of the main model used nowadays to assess the stance of fiscal policy.
Keywords: E30; E62; H60; 330; structural budget balance; fiscal impulse; business cycle